THE RUSSIAN FEDERAL BUDGET EXPENSES FOR THE STATE SOCIAL POLICY: TRENDS AND PECULIARITIES OF PROBLEM SOLVING UNDER THE MODERN CONDITIONS - I. Davydova (Russian Journal of Economics and Law)
The article views the state budget policy in the direction of the social problems solution, as well as the structure of the federal budget expenditures for social policy.